Optimalisasi Distribusi Beras Gudang Umbul Tengah Menggunakan Metode Transportasi BULOG Cabang Serang - Aryanto Dwi Putra; Kesya Zakia Rachma; Muhamad Hafid Muhajar; Sigit Tamtama; Bambang Hermawan (GLOBAL SCIENTS PUBLISHER, 2026)
This study analyzes the optimization of rice distribution based on warehouse capacity using the transportation method at Perum BULOG Serang Branch, with a case study of the Umbul Tengah Warehouse. The main issue is inefficient rice distribution caused by mismatches between warehouse capacity and regional demand, resulting in high distribution costs. To address this problem, the transportation method in operations research was applied to identify the most efficient distribution pattern. The research stages included determining an initial feasible solution and testing the optimal solution based on warehouse capacity data and regional demand. The results show that 11,500 tons of rice can be distributed evenly from four warehouses to three destination regions. Initial calculations using the North West Corner method produced a distribution cost of Rp1,235,000. Further optimization using the Least Cost Method and Vogel’s Approximation Method reduced the cost to Rp1,195,000. Validation using the Stepping Stone method confirmed that no alternative distribution routes could further reduce the cost, indicating that Rp1,195,000 is the optimal distribution cost. Therefore, the transportation method can be used as a decision-making tool in managing rice distribution at Perum BULOG Serang Branch to improve operational efficiency and support food security.